Spelling Compliance and Institutional Professionalism: A Sociolinguistic Analysis of Official Documents in Indonesian Local Government - Huplan Huplan; Yessi Fitriani; Puspa Indah Utami (Journal of Social Work and Science Education, 2026)
This study examines compliance with the General Guidelines for Indonesian Spelling (PUEBI) in official documents from the Palembang City Education Office and analyzes the sociolinguistic implications of spelling errors for institutional professionalism. Using qualitative content analysis of 20 official documents (official letters, memos, circulars, and activity reports) and semi-structured interviews with document preparers, we identified 152 spelling violations across six error categories. Word writing errors (28%), non-standard loanwords (17%), and punctuation mistakes (15%) were most prevalent. Critically, we documented serious errors including misspelled city names ("Palembang"), date inconsistencies, and invalid employee identification numbers errors that fundamentally undermine document credibility. Sociolinguistic analysis reveals these errors reflect a weak culture of linguistic accuracy and inadequate internalization of standard language ideology within bureaucratic practice. The findings suggest that spelling non-compliance is not merely technical but signals institutional attitudes toward language as a marker of professionalism. We recommend targeted language training, development of internal style guides, and strengthened editing protocols to enhance both linguistic quality and institutional image.